Comparison of varying pollen source on productivity of sour cherry (Prunus cerasus L.) cultivars - Davarynejad, G. H.; Nyéki, J.; Szabó, T.; Tornyai, J.; Szabó, Z.; Soltész, M.; Davarynejad, E. (International Journal of Horticultural Science, 2010)
Fruit set of five sour cherry cultivars (‘Újfehértói fürtös’, ‘Éva’, ‘Petri’, ‘Pándy 279‘ and ‘Csengôdi’) of eight years-old trees grown in Újfehértó, located in the Eastern north part of Hungary have been studied over two years (2008 & 2009). Following reciprocally cross-pollination, free-pollination, self-pollination (autogamy) artificial self-pollination (geitonogamy) were studied. The results show that both maternal and paternal parent cultivates had significant effects on the percentage fruit set. Significant differences have been found in fruit set among years and among pollination treatments. Fruit set of free-pollinated Pándy 276 cultivar was low and seasonally highly variable. The yield of this cultivar on self-pollinated flowers was nearly 0%, and in this treatment the maximum yields did not reach 10% in any of the examined cultivars. There was no significant relationship in the fruit set of free-pollination and natural self-pollination treatments.